1997
DOI: 10.1016/s0266-7681(97)80061-7
|View full text |Cite
|
Sign up to set email alerts
|

Skin Replacement in Dupuytren’s Disease

Abstract: We have reviewed 90 rays in 67 patients who had undergone radical digital dermofasciectomy. Follow-up was from 24 to 100 months. Problems with skin grafts, moving two-point discrimination and active range of joint movement were noted. The recurrence rate in this series was 8%, a very much better figure for disease control than has been reported for standard approaches for Dupuytren's disease. Radical digital dermofasciectomy is strongly recommended for all cases of recurrent Dupuytren's disease requiring reope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 10 publications
0
50
0
4
Order By: Relevance
“…Clinically, full-thickness skin grafts (in which the dermis is included) have been shown to attenuate recurrence of DD in some studies [7,[74][75][76], implying that local environment of the DD cord left behind after resection may contain factors that promote disease recurrence. Our in vitro data suggest that PF fibroblasts, derived from the palmar fascia immediately adjacent to DD cord, are sensitive to periostin-induced proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, full-thickness skin grafts (in which the dermis is included) have been shown to attenuate recurrence of DD in some studies [7,[74][75][76], implying that local environment of the DD cord left behind after resection may contain factors that promote disease recurrence. Our in vitro data suggest that PF fibroblasts, derived from the palmar fascia immediately adjacent to DD cord, are sensitive to periostin-induced proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the literature, which suggests that recurrence of Dupuytren disease occurs less frequently in patients who have had a dermofasciectomy. 12, 13 Tonkin et al 14 compared outcomes in 100 patients treated by dermofasciectomy and fasciectomy and found that the rate of disease recurrence in the former group was dramatically reduced. Tonkin et al 9 also reported that amputation specimens following dermofasciectomy showed no histologic recurrence of the disease under the skin graft.…”
Section: N Dermofasciectomymentioning
confidence: 99%
“…L'excision de la peau avec la lésion et son remplacement par une greffe cutanée ou partiellement par un lambeau local (latérodigital, intermétacarpien palmaire) semble être seule capable d' éviter ou de diminuer les récidives [10], valant parfois le qualificatif de « pare-feu » à la greffe. Plusieurs études ont montré la réduction [11][12][13], voire l'absence [1,[14][15][16][17][18] de récidive avec dermofasciectomie et greffe de peau. Ces auteurs recommandent d'ailleurs d'utiliser cette technique d'emblée dans les formes agressives [11][12][13] ou secondairement dans les formes récidivantes [12,15,[17][18][19].…”
Section: Discussionunclassified